"The Community Helped Me:" Community Cohesion and Environmental Concerns in Personal Assessments of Post-Disaster Recovery. Issue 3 (3rd March 2020) - Bergstrand, Kelly; Mayer, Brian
Abstract: This study investigates long-term appraisals of community recovery after a major environmental disaster. Specifically, we conducted a survey of 351 individuals living in coastal counties in Alabama and Florida on the five-year anniversary of the Deepwater Horizon oil spill. Using mixed methods that combined content analysis and ordinary least squares regression, we find that residents who believe they live in a community where neighbors help each other are more likely to see their communities as recovering. Conversely, reporting major effects from environmental problems, like lost fishing income, reduces perceptions of community recovery. Five years after the oil spill a majority of respondents saw little economic recovery and almost half perceived low environmental recovery. This reflects the importance of the environment to the long-term health and success of areas dependent on natural resources. It also suggests the need for directing funding toward community-level programs and preserving shared natural resources post-disaster.